Kunststudenten : Studienarbeit - Barlang, Wolfgang (Braunschweig : Hochschule für Bildende Künste Braunschweig, 1982)
Rokahr, Burkhardt ; Weingärtner, Robert ; Stegentritt, Ulrike ; Harke, Peter ; Arfaras, Michalis ; Krantz, Regina ; Bloss, Elsa ; Barlang, Wolfgang ; Rank, Margarete ; Ngo Tan, Dung ; Emde, Barbel ; Paproth, Gerhard ; Eckardt, Peter ; Adler, Eckard ; Anwander, Rainer ; Lengfeld, Cornelia ; Reimann, Frank ; Kaven, Bernd ; Kuck, Jürgen ; Gendolla, Barbara
boek